2019
DOI: 10.1080/13573322.2019.1567485
|View full text |Cite
|
Sign up to set email alerts
|

High School students’ experiences of being ‘seen’ by their physical education teachers

Abstract: The study examines the association between students' level of physical fitness and experiences of being "seen" by their physical education (PE) teachers, by interviewing 26 high school students (13 with low physical fitness, and 13 with high physical fitness). The analyses indicated that being seen in PE seems to be related to experienced opportunities for students to display their skills, teachers' caring behaviors, feedback from teachers, and the quality and tone of dialogue with teachers. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 12 publications
5
23
0
2
Order By: Relevance
“…The interviews indicated that the boys felt that they were seen differently by the PE teacher than when they were in more gender-balanced classes. That the respondents in this study experienced being seen as positive is in agreement with Lagestad et al (2020) . In Lagestad (2017) , a girl who was the only girl in her high school class reported that she was seen by the PE teacher but that she experienced this as negative.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The interviews indicated that the boys felt that they were seen differently by the PE teacher than when they were in more gender-balanced classes. That the respondents in this study experienced being seen as positive is in agreement with Lagestad et al (2020) . In Lagestad (2017) , a girl who was the only girl in her high school class reported that she was seen by the PE teacher but that she experienced this as negative.…”
Section: Discussionsupporting
confidence: 81%
“…In Lagestad (2017), a girl who was the only girl in her high school class reported that she was seen by the PE teacher but that she experienced this as negative. Another study suggested that having a high activity level, such as our respondents had, was a good means of being noticed by the PE teacher (Lagestad et al, 2020). To this extent, this supports the findings of this study.…”
Section: Easier To Show Offsupporting
confidence: 87%
See 1 more Smart Citation
“…PA patterns among individuals with ID, but research focusing on attitudes, motivation and experiences of PA and health, and effects of impairment and ableism within individuals with ID is lacking (Apelmo, 2021;Mundhenke et al, 2010). Research (Lagestad et al, 2019) in Scandinavia raise that one of the aims in PE is to educate humans to be healthy and productive citizens, whereas other research (Dowling, 2016) has identified that PE seems to have limited influence on adolescent's time outside school. This actualises the impact of PE and the importance of strengthening the focus on PA also within the lives of young individuals with ID.…”
Section: Introductionmentioning
confidence: 99%
“…The questions used to assess happiness, mastery, well-being and contentment had been specifically developed for PE and PA research, and had been used earlier in the REPAC project (Säfvenbom et al, 2018 ). Whilst these questions are closely connected to these variables, they also connect to self-determination as a theoretical framework based on; basic psychological needs (Vlachopoulos and Michailidou, 2006 ), motivation (Guay et al, 2000 ), belonging (Anderson-Butcher and Conroy, 2002 ) and enthusiasm (Lagestad et al, 2019 ). Each question/statement offered alternative answers on a 1-7 Likert scale.…”
Section: Methodsmentioning
confidence: 99%